2015
DOI: 10.1016/j.immuni.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 4 Engagement on Dendritic Cells Restrains Phago-Lysosome Fusion and Promotes Cross-Presentation of Antigens

Abstract: The initiation of cytotoxic immune responses by dendritic cells (DCs) requires the presentation of antigenic peptides derived from phagocytosed microbes and infected or dead cells to CD8(+) T cells, a process called cross-presentation. Antigen cross-presentation by non-activated DCs, however, is not sufficient for the effective induction of immune responses. Additionally, DCs need to be activated through innate receptors, like Toll-like receptors (TLRs). During DC maturation, cross-presentation efficiency is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 39 publications
4
159
0
Order By: Relevance
“…One example is the TLR4 agonist LPS, whose effect on phagosome maturation kinetics is time dependent: short stimulation of DCs with LPS (up to 6 h) does not alter phagosomal antigen degradation, while intermediate (8–18 h) and long (20–40 h) stimulations induce a delay in phagosomal antigen degradation [33]. This is achieved by the perinuclear clustering of lysosomes, which is controlled by Rab34, leading to reduced phagolysosomal fusion.…”
Section: Impact Of Immune Signals On Phagosome Maturationmentioning
confidence: 99%
“…One example is the TLR4 agonist LPS, whose effect on phagosome maturation kinetics is time dependent: short stimulation of DCs with LPS (up to 6 h) does not alter phagosomal antigen degradation, while intermediate (8–18 h) and long (20–40 h) stimulations induce a delay in phagosomal antigen degradation [33]. This is achieved by the perinuclear clustering of lysosomes, which is controlled by Rab34, leading to reduced phagolysosomal fusion.…”
Section: Impact Of Immune Signals On Phagosome Maturationmentioning
confidence: 99%
“…Throughout our studies, we used endotoxinfree chicken OVA as a model protein antigen since OVA has been widely used in initial vaccine development studies as well as in studies examining the mechanisms of crosspresentation. 12,[19][20][21]36,37 BMDCs were pulsed with soluble OVA in the presence or absence of CLs. After overnight + T-cells isolated from OT-I transgenic mice that only have CD8…”
Section: Cls Enhance Antigen Cross-presentation By Bmdcsmentioning
confidence: 99%
“…[9][10][11] Importantly, CLs can also enhance antigen cross-presentation 12,13 -the process by which APCs phagocytose extracellular protein antigens, process them intracellularly into peptide epitopes, and present them in the context of major histocompatibility complex-I (MHC-I) on the The specialized role of DCs in cross-presentation is supported by their unique characteristics, including their mildly degradative phagosomes compared to those of other phagocytic cells, such as macrophages; shuttling of endosomal protein antigens to the cytosol for subsequent processing via proteasomes for antigen degradation; and efficient loading of the processed antigen peptides onto MHC-I molecules via either endoplasmic reticulum (ER) or vacuolar endosomal pathways. [16][17][18][19][20][21] Prior studies have also suggested that DCs exhibit a delayed process of acidification and maturation of endolysosomes, which inhibit the activities of lysosomal proteases and deter antigen degradation. [21][22][23][24] This would allow antigens to be "rescued" from excessive degradation and shuttled to intracellular compartments for complexation with MHC-I molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of a CD4 T cell response is largely determined by pathogen detection by DCs that present antigens to naïve T cells to initiate an adaptive response. DCs can also be activated to efficiently cross-present extracellular antigens on MHC-I, leading to activation of CD8 T cells (144, 145). …”
Section: Dysregulation Of Adaptive Immunity and Chronic Inflammationmentioning
confidence: 99%